Mediasi Corporate Image pada Hubungan Price Policy dengan Keputusan Pembelian - Elvirra Ariska Dewi; Pudjo Sugito (Fakultas Ekonomi, UIN Maliki Malang, 2021)
Abstract: This research on the effect of price policy on purchasing decisions through corporate image mediation aims to analyze how much influence is generated by the price policy mediated by corporate image on purchasing decisions. To achieve this goal, the research method used is quantitative. The sampling technique uses accidental random sampling technique and the number of samples used is 100 respondents. Data analysis techniques using SmartPLS. The independent variable in this study is the price policy while the dependent variable is purchasing decisions, and the corporate image mediation variable. Primary data is obtained through Matahari Department Store visitors and of course the local community. Based on data analysis, it is revealed that the price policy does not significantly affect on purchasing decisions. However, the pricing policy significantly effect on corporate image. Meanwhile, corporate image significantly affect on purchasing decisions and price policy significantly effect on purchasing decisions that are mediated by corporate image. The findings of this research provide interesting information because corporate image not only affects purchasing decisions, but also mediates the effect of price policies on purchasing decisions.